Correlation Between Anti-Topoisomerase I and C-Reactive Protein Antibody Level with Modified Rodnan Skin Score On Systemic Sceloris Patients - Sumartini Dewi; Wisynu Tresnadi A.B; Rachmat Gunadi Wachjudi (Indonesian Rheumatology Association, 2020)
A B S T R A C TSystemic sclerosis is characterized by extensive and progressive organfibrosis processes leading to organ failure and death. Modified Rodnan SkinScore (mRSS) had been used as a clinical parameter of skin fibrosis. Anti-topoisomerase I and C-Reactive Protein (CRP) are potential biomarkers forassessing disease activity. The study was performed to determine theassociation of anti-topoisomerase I and CRP antibodies with mRSS values.We performed an observational analytic study based on primary andsecondary data. Systemic sclerosis patient sera data was obtained fromDewi S et al's study, taken from May 2015 to June 2017. Serum Anti -topoisomerase I antibody and CRP level analysis were performed inDecember 2017.Fifty six samples analyzed. Fifty four subjects (96.4%) out of 56 subjects arewomen with an average age of 37 ± 11 years, 41 subjects (73.3%) hasdisease duration over 2 years, 34 subjects (60.7%) has difuse systemicsclerosis, 41 subjects (73.3%) in steroid therapy and 50 subjects (89.3%) inmethotrexate therapy. The statistical analysis showed no correlationbetween anti-topoisomerase I antibody and CRP levels with mRSS values(r = 0.205, p = 0.064; r = -0.134, p = 0.167), but there was a positivecorrelation of anti-topoisomerase I antibody level with mRSS (r = 0,422 p =0,007) and negative correlation between CRP level and mRSS (r = -0,511 p= 0,001) in diffuse sclerosis systemic.From this study we concluded that anti-topoisomerase I antibody and CRPlevel were not correlated with mRSS, but in patient with diffuse systemicsclerosis there was a positive correlation of anti-topoisomerase I antibodylevel with mRSS and negative correlation between CRP level and mRSS.